(untitled) (Journal of Rangpur Medical College, 2024)
Background: Dengue fever, particularly in its severe form, poses a significant health challenge in tropical regions like Bangladesh. Understanding the clinical and laboratory predictors of mortality in pediatric patients with severe dengue is crucial for improving management strategies and patient outcomes. Methods: This cross-sectional analytical study was conducted at the Department of Pediatrics, Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh, from January 2019 to December 2020. It included 300 pediatric patients diagnosed with severe dengue. Results: Of the 300 participants, 286 (95.33%) survived, while 14 (4.67%) succumbed to the disease. Major bleeding, refractory shock, a significant rise in hematocrit, signs of pleural effusion, and ascites were significantly associated with mortality. Hematologically, a low platelet count (<15000/mm3) was a strong predictor of mortality. Elevated serum ferritin levels (>500 micrograms/L) were also significantly associated with increased mortality risk. Conclusions: The study highlights major bleeding, refractory shock, significant hemoconcentration, pleural effusion, ascites, low platelet count, and high serum ferritin levels as key predictors of mortality in pediatric patients with severe dengue. These findings underscore the need for comprehensive clinical monitoring and targeted management strategies to improve outcomes in pediatric dengue patients. J Rang Med Col. March 2024; Vol. 9, No. 1:10-15